2018
DOI: 10.5539/gjhs.v10n12p96
|View full text |Cite
|
Sign up to set email alerts
|

Socio-Economic Status, Hygiene Practices and Microbial Exposure of the Waste Collectors of Dhaka City in Bangladesh

Abstract: Waste is a discarded part generated from primary use of a material. In most cases, waste is very much unwanted and unusable but may be usable and beneficial for our economy and environment. Waste collectors are playing vital roles for the management of wastes though they are deprived of their basic needs. They are involved directly or indirectly to our economy and environmental development. However, whether waste collection activity has any effect on the socioeconomic status, hygiene practices, and microbial e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…It is reported that almost 75.60% of people disposing of all types of waste together in a specific area or a community waste disposal point, which may create the health hazard of waste workers. Infectious pathogens may easily infect waste collectors in the country, as they are often not well equipped to handle hazardous waste and do not always follow safety protocols (Islam et al 2016 ; Rifat et al 2018 ; Alam and Qiao 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…It is reported that almost 75.60% of people disposing of all types of waste together in a specific area or a community waste disposal point, which may create the health hazard of waste workers. Infectious pathogens may easily infect waste collectors in the country, as they are often not well equipped to handle hazardous waste and do not always follow safety protocols (Islam et al 2016 ; Rifat et al 2018 ; Alam and Qiao 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…During work, all scavengers maintain contact as usual such as shaking hands, smoking, eating street food without washing hands. Their poor personal hygiene practices may also be a potential risk factor for their disease (Rifat et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, homelessness and dependency on street vended foods leave them, especially SWCs, in serious food insecurity. It was found that their average daily income was only BDT 150 (approximately 1.9 USD) (Rifat et al, 2018). Waste collectors in other countries such as India and Nepal were found to smoke cigarette, tobacco and to drink alcohol (Salve & Bansod, 2017).…”
Section: Figure 1: Body Mass Index (Bmi) Of the Respondents As Categorized By Dietary Practices (N=130)mentioning
confidence: 99%